Studies on Preparation and Catalytic Performances of Monolithic Solid Acid Catalysts - Huang, Kai; Lu, Keqiang; Ni, Songbo; Tong, Shaoping (Asian Journal of Chemistry, 2011)
In order to facilitate separation and recycling, a novel SO42-/ZrO2-TiO2/cordierite monolithic catalysts were prepared by dip-coating method and sol-impregnation method. The adherent stability of the catalyst was measured by ultrasonic wave and thermal oscillation. The surface morphology and crystalline structure were separately characterized by SEM and XRD. The acid treatment results showed that the weight loss rate of cordierite support can reach 4.53 % by 30 % oxalic acid solution impregnated for 6 h, which was the suitable acid treatment condition. The study of monolithic solid acid prepared by different methods demonstrated that the catalyst prepared by sol-impregnation method exhibited better adherent and thermal stability than dipcoating method. The weight loss rate was less than 1 % by ultrasonic wave and thermal oscillation and the n-butyl acetate esterification yield was 75 %. The SEM images of monolithic catalyst prepared by sol-impregnation method showed that the particle size on the catalyst surface was more uniform and regular. The catalyst prepared by sol-impregnation method appeared a complete anatase TiO2 and mainly tetragonal ZrO2 from the XRD spectra.